Integrating SERVQUAL and QFD Framework for Product and Service Design. Case Study: Beehive Cafe Bandung - Apriani, Dini; Lestari, Yuliani Dwi (Journal of Business and Management, 2015)
Abstract. Recently, the growth of café and restaurant industry was increased in Indonesia. Thus, every café and restaurant offer unique concept and innovative product and service to customer. This condition would create the competition that higher than before, and it likely could make possibility to loss the market. Therefore, in competing with the competitors, a café should consider the appropriate design of product and service to fulfill customer expectation. Customer expectation could influence the revenue of café and restaurant, so the quality of product and service that suitable with the expectation can keep the current market and capture potential market.By deploying questionnaire to 105 respondents that consists of current customer and potential customer of Beehive café, this research could define specification to describes the VOC. Additionally, this questionnaire applied the principal of SERVQUAL’s dimensions namely tangible, reliable, responsible, assurance and empathy. After the VOC defined, this research conducted QFD framework from defining voice of customer (VOC) until technical evaluation. Moreover, this research contributed in two points: (i) propose appropriate design for product and service in Beehive café in order to meet customer needs and desires, (ii) provide the priorities of project improvement should be taken by Beehive café to fulfill customer expectation and to compete with other competitors.The fundamental result of this research is Beehive café has 12 factors of VOC that should be completed by 29 specifications of technical characteristics. Besides that, if compared with other competitors Beehive café still did not serve product and service suitable with customer expectation. However, in technically Beehive café had good specification of technical characteristics to answer VOC, but in practically Beehive could not optimize these specifications to fulfilled expectation of customer. On the other word, this research can help Beehive café to determine what will satisfy the customer and where to deploy the effort in urgent improvement. Keywords: Quality Function Deployment, SERVQUAL, Voice of Customer, and Customer Expectation